Exploring the roles and functions of champions within community-based interventions to support older adults with chronic conditions: A scoping review protocol. - Kristina M Kokorelias; Hardeep K Singh; Reham Abdelhalim; Marianne Saragosa; Guillaume Lim Fat; Christine Sheppard (PLoS ONE)
Background Health care solutions are needed to meet the need of an ageing population. Health care champions are people who endorse the adoption of new initiatives being implemented within health care settings. Although the role of champions has been cited as key to the success of numerous community-based interventions implemented to improve the care of older adults with chronic conditions, no synthesis of their implementation experiences have been conducted. We report on a scoping review protocol that will be applied to collect evidence on the role of champions within community-based health interventions to support older adults with chronic conditions. Specifically, we will identify how the term 'champion' is used and defined (i.e., conceptualized) and identify the roles (i.e., professional background) and functions of champions (i.e., responsibilities). We will also explore how this role impacts program implementation. Methods This is a scoping review protocol informed by guidelines for Scoping Reviews (PRISMA-ScR) and a six-stage scoping review methodology. Peer-review literature will be retrieved from Medline, CINAHL, PubMed, PsycInfo, Cochrane JBI and Scopus databases, using a peer-reviewed search strategy developed in collaboration with an Information Specialist. The scoping review will consider all empirical studies published in English. Two reviewers will pilot-test the screening criteria and data abstraction forms, and then independently screen the literature. Extracted data will be analyzed numerically and thematically. Self-identified champions will be consulted to refine the practice recommendations from this work. Discussion This scoping review will broadly and systematically identify, define and expand existing knowledge on champions' impact in implementing community-based interventions to support older adults with chronic conditions. We anticipate that our results will lead to a greater understanding of the characteristics and role champions play within these interventions, which will be relevant to a wide range of knowledge users, including researchers, decision-makers, and health care providers.